EFFECTS OF COLD-WATER IMMERSION (≤14°C) ON PHYSIOLOGICAL RECOVERY, INFLAMMATION, AND PERFORMANCE: A SYSTEMATIC REVIEW OF HUMAN STUDIES - Stanisław Rogiński; Marta Brzęcka; Antoni Liebert; Karol Krupiniewicz; Marek Wojciechowcz; Miłosz Rogiński; Mariusz Suchcicki; Łukasz Chojnowski; Katarzyna Mazurek; Anna Dominiczak (International Journal of Innovative Technologies in Social Science, 2026)
Background: Cold-water immersion (CWI) is a widely used recovery strategy among athletes and physically active individuals, commonly applied to reduce post-exercise fatigue and muscle soreness. Although CWI is known to induce rapid thermoregulatory and autonomic responses, the magnitude and direction of its effects appear strongly dependent on protocol parameters such as water temperature, exposure duration, and immersion depth. Evidence remains fragmented, and many previous reviews have combined cold modalities above 14°C or non-immersion cryotherapies, limiting clarity regarding true cold-water exposure.Aim: This review synthesizes current evidence regarding the physiological and performance-related effects of CWI performed at ≤14°C for ≥1 minute in healthy adults, with particular focus on recovery, inflammatory and immune responses, cardiovascular function, and neuromuscular performance.Methods: We systematically searched PubMed, Google Scholar, and Cochrane Library using terms including cold water immersion, CWI, ice bath, cold-water immersion recovery, cold immersion muscle soreness, cold immersion performance, and related combinations. Only open-access human experimental studies reporting direct immersion ≤14°C were included. Twenty studies met the eligibility criteria.Results: CWI consistently reduced delayed-onset muscle soreness and improved subjective recovery across protocols. Performance outcomes were variable: benefits were more evident in high-intensity and intermittent sports, whereas strength and endurance recovery showed mixed results. Inflammatory, immune, and oxidative markers demonstrated context-dependent modulation. Cardiovascular and metabolic responses increased with lower temperatures and longer exposures, and limited evidence suggests potential adaptive effects following repeated immersion.Conclusion: CWI at ≤14°C is an effective modality for reducing muscle soreness and enhancing perceived recovery post-exercise, with conditional benefits for performance depending on protocol and sport type. Physiological responses are heterogeneous, underscoring the need for standardized protocols and further longitudinal research to clarify dose–response relationships and long-term adaptive outcomes.